2022
DOI: 10.3389/fmats.2021.810535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Incorporation on the Reaction Process and Reaction Products of Hydrated Magnesium Silicate

Abstract: In this study, we investigated the impact of aluminium ion (Al3+) incorporation on the microstructure and the phase transformation of the magnesium silicate hydrate system. The magnesium silicate hydrate system with aluminium was prepared by mixing magnesium oxide and silica fume with different aluminium ion contents (the Al/Si molar ratios of 0.01, 0.02, 0.05, 0.1, 0.2) at room temperature. The high degree of polymerization of the magnesium silicate hydrate phases resulted in the limited incorporation of alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…When the MS-MR was 2.0, the main reaction product was forsterite. As the MS-MR increased, the magnesium silicate mineral changed from a chain structure to an island structure, which further showed that Mg atoms mainly played the role of bond breaking in the M-S-H gel, consistent with previous results [23][24][25].…”
Section: Maas At High Temperaturesupporting
confidence: 91%
“…When the MS-MR was 2.0, the main reaction product was forsterite. As the MS-MR increased, the magnesium silicate mineral changed from a chain structure to an island structure, which further showed that Mg atoms mainly played the role of bond breaking in the M-S-H gel, consistent with previous results [23][24][25].…”
Section: Maas At High Temperaturesupporting
confidence: 91%
“…Hydrotalcite and zeolites were also observed in MgO and SiO 2 cements containing a high NaAlO 2 content [57], while at low amounts of NaAlO 2 and pH values below 10, no zeolites were observed, only hydrotalcite/Al(OH) 3 [50]. In any cases, the presence of extra Al-containing phases limited the Al incorporation in M-S-H. Also Jia et al [58] observed a limitation of Al/Si (< 0.05) in M-A-S-H in the presence of aluminium nitrate in the MgO-SiO 2 system. In most of the cases, the exact incorporation of Al in M-A-S-H is extremely difficult to quantify due to the nanocrystallinity of the Alcontaining phases, either Al-hydroxides, hydrotalcite-like phases, N-A-S-H gels or M-A-S-H.…”
Section: Structure and Formation Of M-s-h Structure Of M-s-hmentioning
confidence: 91%
“…In response to China's environmental policy, the development of new cementitious materials with complementary properties and environmental characteristics of traditional cement has become the research direction of the low-carbon cement industry, and, in this direction, magnesium oxide-based cementitious materials are of great importance. As a new type of green high-performance building material [1], magnesium oxide-based cementitious materials not only have good cementitious properties, but also have the characteristics of a low-pH alkali environment, high strength, and fast molding; besides, it is widely used in the curing of heavy metal ions and the comprehensive utilization of industrial solid wastes [2][3][4][5]. The development and research of magnesium oxide-based cementitious materials can aid in the rational utilization of abundant magnesium-based resources and idle industrial wastes, which are in line with China's national strategy for sustainable development, and have a wide range of potential applications.…”
Section: Introductionmentioning
confidence: 99%